New and unusual causes of foot drop - Cengiz Aldemir; Fatih Duygun (Medicine Science, 2017)
Several reasons for foot drop have been reported in literature. In recent years, innovations have been added associated with some current treatment methods. The study comprised 12 patients who presented with foot drop, with rarely seen or not previously encountered causes. The patients comprised 6 males and 6 females with a mean age of 41.25 years (range, 18-72 years). The etiology of the foot drop which developed in the patients was after taking the peroneus longus tendon as autograft with a tendon stripper in 2 cases, after revision total knee arthroplasty in 1 case, after primary total knee arthroplasty in 2 cases, after a fall while playing football in 1, after injection in 3, secondary to bilateral compartment syndrrome in 1, after lying in a lateral position for a long time during a kidney operation in 1 and following a burn injury in 1 case. Of the total 12 patients, transfer of the tibialis posterior tendon to the anterior was applied in 4 cases. Decompression and fasciotomy was applied to 2 cases. In 3 cases, surgical tendon transfer was recommended but the patients rejected this treatment. Conservative follow-up was applied to 3 cases. The 4 patients applied with tendon transfer returned to daily activities problem-free. In the 2 cases applied with decompression and fasciotomy, full sensory and motor functions returned to normal in the 15th and 16th week. The motor and sensory functions of the 3 patients followed up conservatively returned to normal in the 14th-15th weeks. Foot drop is the result of an underlying problem rather than a disease per se. New treatment methods applied in orthopaedic surgery may cause the development of unusual foot drop. An awareness of these is necessary together with a detailed anamnesis, examination and laboratory tests to be able to determine the reason and plan treatment. [Med-Science 2017; 6(3.000): 491-5]